2020
DOI: 10.21203/rs.3.rs-31962/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global trends of antimicrobial susceptibility of ceftaroline and ceftazidime-avibactam: a surveillance study from the ATLAS program (2012-2016)

Abstract: Background:This study reports the global trends of antimicrobial susceptibility toceftaroline and ceftazidime-avibactam using data from the Antimicrobial Testing Leadership And Surveillance (ATLAS)programbetween2012and2016.Methods:For the 2012-2016 ATLAS program, 205 medical centers located in Africa-Middle East (n=12), Asia-Pacific (n=32), Europe (n=94), Latin America (n=26), North America (n=31), and Oceania (n=10) consecutively collected the clinical isolates. Theminimum inhibitory concentrations (MICs) and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The study reported susceptibility of CR-E. coli to be 72.3% using Clinical Laboratory and Standards Institute (CLSI) breakpoints against ceftazidime-avibactam. Similarly, susceptibility of CR-K. pneumoniae was reported to be 85.6% using CLSI breakpoints [18].…”
Section: In Vitro Activitymentioning
confidence: 98%
“…The study reported susceptibility of CR-E. coli to be 72.3% using Clinical Laboratory and Standards Institute (CLSI) breakpoints against ceftazidime-avibactam. Similarly, susceptibility of CR-K. pneumoniae was reported to be 85.6% using CLSI breakpoints [18].…”
Section: In Vitro Activitymentioning
confidence: 98%
“…aeruginosa producing different carbapenemases: among Enterobacteriaceae , KPC‐producing strains were resistant to CAZ/AVI at 1.5%, and NDM‐producing strains at 99.6%, while among P . aeruginosa , KPC‐producing strains were resistant to CAZ/AVI at 35.7% and NDM‐producing strains at 97% (Table 1; Kiratisin et al, 2021; H. Zhang, Xu, et al, 2020).…”
Section: Prevalence Of Caz/avi‐resistant Bacteriamentioning
confidence: 99%
“…By 2017–2019, carbapenem nonsusceptible Enterobacteriaceae bacteria in Latin America increased their resistance rate to CAZ/AVI nearly 1‐fold to 25.3% (Karlowsky et al, 2021). In addition, global resistance surveillance by the ATLAS project from 2012 to 2016 showed that carbapenem‐resistant Enterobacteriaceae had a resistance rate of 57.7% to CAZ/AVI, followed by CREC with a resistance rate of 27.7% to CAZ/AVI (H. Zhang, Xu, et al, 2020). The distribution of resistance rate of CRE to CAZ/AVI in different regions was as follows: the highest resistance rate to CAZ/AVI was 66.6% in the Asia‐Pacific region, followed by Africa‐Middle East (39.5%), Europe (28.0%), and Latin America (18.5%), whose trend was consistent with the 2015–2017 INFORM surveillance system showing the distribution of resistance rates of carbapenem nonsusceptible Enterobacteriaceae to CAZ/AVI (Table 1).…”
Section: Prevalence Of Caz/avi‐resistant Bacteriamentioning
confidence: 99%
“…11,12 This fifth-generation broad spectrum cephalosporin possesses activity against common Gram-positive pathogens found in bacterial skin and skin structure infections and community-acquired pneumonia, including MRSA. 13,14 Additionally, ceftaroline demonstrates activity against respiratory tract Gram-negative pathogens, including Moraxella catarrhalis, Haemophilus parainfluenzae and H. influenzae , along with other enteric bacilli. 15 Efficacy against β-lactam–resistant S. aureus can be explained by the high affinity of ceftaroline for staphylococcal PBPs 1, 2 and 3 and MRSA PBP2a.…”
Section: Introductionmentioning
confidence: 99%